A Pre-Service Teacher's Voice on the Challenges of Google Docs-Based Collaborative Writing - Ilaisya Zanua Terry; Nur Arifah Drajati; Ellisa Indriyani Putri Handayani (EDULANGUE, 2021)
The present study recollected a pre-service teacher’s experience in bringing a Web 2.0 tool, Google Docs, for the first time to teach eight junior high school students to write a descriptive text collaboratively in an online environment with the objective of digging in its challenges and eventually reported them in the form of an autobiographical narrative research. Self-study was adopted to gain better understanding about ourselves as educators. The author of this study was a pre-service teacher who is also an English tutor. She is a native speaker of Indonesia and a non-native speaker of English. The data was drawn from various sources to address the trustworthiness of this study. The main data was taken from journal entries the author kept for a period of two months when planning, implementing, and evaluating Google Docs-Based collaborative writing (CW). The other data was derived from artefacts that the pre-service teacher collected during the online teaching and learning process such as a video recording when she explained the lesson, screenshots of casual chatting between her and her students, screenshots of students’ collaborative writing process on Google Docs, and students’ works. The data was examined to identify recurring and salient themes. The results revealed seven challenges found by a pre-service teacher when teaching with Google Docs-based collaborative writing.